The impact of the digital economy on industrial structure upgrading and sustainable entrepreneurial growth - Deevi, Durga Praveen; Allur, Naga Sushma; Dondapati, Koteswararao; Chetlapalli, Himabindu; Kodadi, Sharadha; Perumal, Thinagaran (Springer, 2024)
The financial activity generated by millions of routine online interactions between individuals, businesses, gadgets, information, and procedures is called the “digital economy.” The way businesses function and communicate with one another is changing quickly owing to the digital economy, which gives entrepreneurs new business options with sustainability. This article proposed the effect of the Digital Economy on Industrial Structure Upgrading with Sustainable Entrepreneurial Growth as a mediating factor (DE-ISU-SEG). The article begins by outlining the theoretical underpinnings of the DE and underlining its ability to change the industrial structure of economies. The influence of the DE on ISU and the mediating effect of entrepreneurial growth is then demonstrated empirically through hypothesis development. This paper sought to validate the DE and SEG to support the ISU and the truth of the viable path. It sought to address the issue of inadequate energy for improving China’s local industrial structure in light of the effects of the DE through SEG. This paper primarily utilized statistical analysis with multiple variables and detailed assessment techniques. The paper’s statistical foundation has been data collected from 25 Chinese regions between 2014 and 2022. The findings support that the DE’s growth positively impacts the ISU. They demonstrate how vital the mediator role of SEG is in the evolution of the DE, promoting the modernization of industries. Using a fixed impact model, a mediation effect model, and a threshold regression model, this study examined DE development’s impacts and propagation processes on the transformation and ISU. The findings support that the DE’s growth contributes to the ISU’s promotion and demonstrates the importance of the SEG’s intermediate function in this process. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2024.